The effects of contextual meaning aspects on reading comprehension - Mirza, Akhmad Ali (Journal on English as a Foreign Language (JEFL), 2011)
The study is aimed at investigating the effects of contextual meaning aspects on reading comprehension, and finding out whether or not there is effect of reading proficiency, consists of low and high, on reading comprehension and effect of contextual meaning aspects together with reading proficiency on reading comprehension. It was used experimental design in this study. The data were processed and analyzed according to these steps: giving the treatment, checking and scoring, tabulating, analyzing the data by using statistic technique of ANOVA, and making the conclusion based on the analysis. The number of the sample was 34 students of the students of English education study program of Palangka Raya University. The findings show that example clues considered as the easiest and appositive clues as the most difficult of three context clues in this study. Based on the result, it can be concluded that there is significant effect for contextual meaning aspects and reading proficiency on reading comprehension; however, there is no significant effect of contextual meaning aspects together with reading proficiency on reading comprehension.